Failed treatment of long bone nonunions with low intensity pulsed ultrasound - Biglari, Bahram; Yildirim, Timur Mert; Swing, Tyler; Bruckner, Thomas; Danner, Wolfgang; Moghaddam-Alvandi, Arash (Archives of orthopaedic and trauma surgery, 2016)
IntroductionThe use of low intensity pulsed ultrasound (LIPUS) in the treatment of nonunions is still controversial. The present study is concerned with whether this procedure has a clinical use and which cofactors influence its therapeutic results.MethodsIn this prospective, single institution, observational study, data from October 2010 to October 2013 from 61 nonunions in 60 patients treated with EXOGEN® LIPUS therapy were analysed. The average age was 45.4 ± 9.81 (18-63) years. Treatment was primarily done on long bones of the lower extremity (75.4 %). All 61 nonunions were examined after treatment, and the rate of healing as well as functional and subjective results were evaluated. Based on clinical and radiological findings, patients were divided into two groups: G1—successful treatment; and G2—unsuccessful treatment. Groups were compared to one another to identify possible factors influencing treatment.ResultsTwenty (32.8 %) patients showed bone consolidation with an average time of healing of 5.3 (2-7) months. In patients without successful treatment, who underwent revision surgery instead, full weight bearing took on average 3.7 months longer, and they were able to return to work 6.8 months later. Most of the treated patients (70.5 %) reported no improvement in pain. In G2, 12 (29.3 %) patients suffered in their previous history from osteitis; in G1 there were only two patients (10 %) (p = 0.012). There were further significant differences in the age of the fracture, the type of osteosynthesis, the gap size, as well as the NUSS score.ConclusionDespite patients being chosen strictly according to EXOGEN® indications, only a small number of patients with nonunions who underwent LIPUS therapy experienced successful treatment (32.8 %). Overall, its use resulted in a clear delay in the time of treatment, so that according to our results, the use of LIPUS should be seen critically in long bone nonunions and use should be made on a case-by-case basis.
Gesehen am 11.12.2018